Winnowing Algorithm: A Powerful Tool for Identifying Plagiarism in Assignments - Shrestha, Shiva; Gautam, Sandeep; Sharma, Kiran; Bhandari, Abinay (Journal of Trends in Computer Science and Smart Technology, 2023)
Plagiarism refers to using other ideas or works as their own without giving proper acknowledgment. The act of plagiarism is inappropriate and untrue for many reasons, especially in the academic world. Academicians are aware of this and try to avoid the act of plagiarism by any means necessary. In the present context, the digital way of teaching and learning is in practice which has more chance of plagiarized content. This research provides plagiarism detection features due to the lack of such features in digital-based teaching-learning activities. This proposed system handles the document in text format and uses Winnowing Algorithm for fingerprinting the assignment documents, and the hashing technique chosen for this algorithm is the Rolling Hash function. The similarity value is calculated using Jaccard coefficient. The test results show the combinations of parameters (n-gram, window length, and the base prime number) for the successful implementation of the system. The system successfully detects plagiarism on student assignments. The overall system is developed by using Python Web Framework Django and MySQL as a database.
Keywords: Plagiarism; Winnowing Algorithm; Rolling Hash Function; Jaccard Coefficient; Python